Developing Engagement and Agency through Project Work - Che Musa, Normazidah; Azman, Hazita; Lie, Koo Yew (AJELP: Asian Journal of English Language and Pedagogy, 2016)
Research into student writing has shown the central role of writing in promoting language acquisition. Written language is seen as a discourse practice that students must gradually learn in their academic endeavour. Writing in a second or foreign language however poses problems to students whose proficiency in the language is still developing. This article reports the result of a qualitative study that examines how participation in content-based project work helps students’ learning. The study is informed by the central premise that views language and literacy learning as situated practices in specific classroom contexts and are acquired as students engage with the subject matter and in specific learning tasks (Zamel & Spack, 2006). Data were collected using focus group interviews, classroom observation and document analysis. Findings of the study indicate that talk around the written text is multilingual and that content-related project work serves as a tool to promote engagement and agency among multilingual learners.